Bergabungnya International Organization for Migration (IOM) Menjadi Agen Migrasi Perserikatan Bangsa Bangsa (PBB) - Juliani Az Zahra; Apriwan; Setyaka, Virtuous (Palito, 2025)
After World War II, Europe was plagued by problems due to population density and the high flow of migrant mobility entering Europe. This phenomenon encouraged countries to form an organization to manage the movement of people and logistics in the European region known as the International Organization for Migration (IOM). Despite being established with a limited, temporary mandate, and outside the UN framework, IOM managed to grow, proving its expertise and role in various global migration events to become one of the leading actors in global migration. However, in 2016, IOM decided to form a more formal bond of cooperation by signing the 2016 Agreement which also marked the incorporation of IOM into the UN, making IOM a "UN Migration Agency". This research explains the reasons for IOM's incorporation into the UN system. This research uses qualitative methods and uses data from secondary sources. The researcher used Principal-Agent Theory which relies on the relationship of delegation of duties and authority. This research emphasizes that IOM's joining was driven by IOM's interest in obtaining resources, such as funding, recognition, expansion of influence, and certain privileges and immunities, to achieve goals in accordance with its global strategy. Keywords: Migration Governance, International Organization for Migration, United Nations